2009
DOI: 10.1001/archneurol.2009.283
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Surgical Outcomes of Patients With Refractory Magnetic Resonance Imaging–Negative Epilepsies

Abstract: To explore several characteristics of patients with pharmacoresistant epilepsy without distinct lesions on magnetic resonance images (MRI − ), who account for a relevant proportion of presurgical patient cohorts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
173
1
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(185 citation statements)
references
References 23 publications
4
173
1
7
Order By: Relevance
“…[5][6][7][8] Despite substantial efforts, the lack of a lesion on MRI has consistently been shown to be one of the predictors for surgical failure. 9,10 Therefore, MRI-negative patients are usually considered unfavorable surgical candidates 4 and are often denied epilepsy surgery. Yet, surgical resection can be effective in well-selected patients with no visible MRI abnormality.…”
mentioning
confidence: 99%
“…[5][6][7][8] Despite substantial efforts, the lack of a lesion on MRI has consistently been shown to be one of the predictors for surgical failure. 9,10 Therefore, MRI-negative patients are usually considered unfavorable surgical candidates 4 and are often denied epilepsy surgery. Yet, surgical resection can be effective in well-selected patients with no visible MRI abnormality.…”
mentioning
confidence: 99%
“…In addition, various neuro-radiological imaging techniques are employed to further identify the structural or functional epileptogenic lesion(s). Multiple studies have shown that the prognosis of epilepsy surgery varies depending on the etiology and location of the epileptogenic zone [43][44][45][46][47][48][49][50][51][60][61][62][63][64]. Radiographically identifiable epileptogenic lesions provide information about the etiology and localization of epilepsy, and can provide prognostic information for focal respective epilepsy surgery.…”
Section: Non-pharmacological Treatmentmentioning
confidence: 99%
“…Radiographically identifiable epileptogenic lesions provide information about the etiology and localization of epilepsy, and can provide prognostic information for focal respective epilepsy surgery. Identifying a structural lesion on MRI provides an excellent prognosis from epilepsy surgery, with 60-90% freedom from disabling seizures [43][44][45][46][47][48][49][50][51][60][61][62][63][64]. Temporal lobe epilepsy is the most common type of epilepsy, and mesial temporal sclerosis (MTS) is the most common temporal lobe epilepsy [65].…”
Section: Non-pharmacological Treatmentmentioning
confidence: 99%
“…It is increasingly recognized that in many NLNE cases, an EZ with underlying focal cortical dysplasia (FCD) may be missed by routine MRI [17,18]. Since nonlesional epilepsy is associated with a poor surgical outcome compared to lesional epilepsy, the use of multimodal imaging for localization of lesions not seen on MRI is essential to identify candidates for epilepsy surgery who are refractory to AED therapy.…”
Section: Introductionmentioning
confidence: 99%